Modern biochemical methods used in the diagnosis of experimental toxic hepatitis - Sayfutdinova Z.A (Zien Journals, 2024)
Oxygen is required by the cells of most organisms to produce sufficient ATP for metabolic activity. Hypoxia, or oxygen deprivation, occurs in human tissues and cells due to a variety of conditions, including heart and lung diseases, anemia, and circulatory disorders. Depending on the severity, irreversible tissue and cell damage may occur
Keywords: Oxygen; diseases; circulatory; cells